2008
DOI: 10.1371/journal.pone.0003721
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of DILP2 in Drosophila Triages a Metabolic Phenotype from Lifespan Revealing Redundancy and Compensation among DILPs

Abstract: The insulin/IGF-like signalling (IIS) pathway has diverse functions in all multicellular organisms, including determination of lifespan. The seven insulin-like peptides (DILPs) in Drosophila are expressed in a stage- and tissue-specific manner. Partial ablation of the median neurosecretory cells (mNSCs) in the brain, which produce three DILPs, extends lifespan, reduces fecundity, alters lipid and carbohydrate metabolism and increases oxidative stress resistance. To determine if reduced expression of DILPs is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
199
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(223 citation statements)
references
References 35 publications
19
199
5
Order By: Relevance
“…Based upn genomic sequence and similarity to mammalian insulin, Drosophila have at least seven candidate IIS ligands. Evidence from RNAi experiments in our lab and published by others, while our work was in progress (34), indicate a high degree of redundancy among DILPs, including compensatory upregulation of expression of dilp gene(s), when others are experimentally downregulated. Thus, multiple approaches will be required to assess the functions of this complex multigene family.…”
Section: Control Of Growth and Metabolism By Iis Is Evolutionarily Comentioning
confidence: 62%
See 1 more Smart Citation
“…Based upn genomic sequence and similarity to mammalian insulin, Drosophila have at least seven candidate IIS ligands. Evidence from RNAi experiments in our lab and published by others, while our work was in progress (34), indicate a high degree of redundancy among DILPs, including compensatory upregulation of expression of dilp gene(s), when others are experimentally downregulated. Thus, multiple approaches will be required to assess the functions of this complex multigene family.…”
Section: Control Of Growth and Metabolism By Iis Is Evolutionarily Comentioning
confidence: 62%
“…One interpretation of the absence of growth defects is that there is functional redundancy among dilps. In keeping with this, a recent paper reported that expression of dilp2 RNAi resulted in a compensatory increase in dilp3 levels (34). With 7 dilp genes, it is virtually impossible to assess functional redundancy using combinations of individual RNAi lines, which may vary in their effectiveness overall or in different cell types.…”
Section: Resultsmentioning
confidence: 99%
“…Drosophila has seven genes encoding insulin‐like peptides (dilps), and ablation of the cells expressing only three of the seven dilps in neuroendocrine cells of the brain is sufficient to increase longevity (Broughton et al ., 2008). dFoxO has also been shown to regulate D. melanogaster aging when activated specifically in the adult pericerebral fat body.…”
Section: Animal Modelsmentioning
confidence: 99%
“…In D. melanogaster adults, IPCs produce three out of the seven encoded ILPs (ILP2, ILP3 and ILP5), which are independently regulated [34,37,38]. ILPs signal through the insulin receptor (INR) to regulate metabolism, growth, reproduction and aging [34,[39][40][41][42][43][44] (Fig.…”
Section: The Endocrine Axis Of Photoperiodismmentioning
confidence: 99%